Efficiency and Safety of Patent Ductus Arteriosus Surgical Ligation in Extremely Low Birth Weight Infants Without Chest Tube Placement - Kourelis, Georgios; Kanakis, Meletios; Loukas, Constantinos; Kakava, Felicia; Kyriakoulis, Konstantinos; Bobos, Dimitrios; Apostolopoulou, Sotiria; Rammos, Spyridon; Giannopoulos, Nikolaos (Journal of Pediatric Intensive Care, 2021)
Patent ductus arteriosus (PDA) has been associated with increased morbidity and mortality in preterm infants. Surgical ligation (SL) is generally performed in symptomatic infants when medical management is contraindicated or has failed. We retrospectively reviewed our institution's experience in surgical management of PDA for extremely low birth weight (ELBW) infants without chest tube placement assessing its efficiency and safety. We evaluated 17 consecutive ELBW infants undergoing SL for symptomatic PDA (January 2012–January 2018) with subsequent follow-up for 6 months postdischarge. Patients consisted of 9 (53%) females and 8 (47%) males. Mean gestational age (GA) at birth was 27.9 ± 2.1 weeks. Median values for surgical age (SA) from birth to operation was 10 days (interquartile range [IQR]: 8–12); PDA diameter 3.4 mm (IQR: 3.2–3.5); surgical weight (SW) 750 g (IQR: 680–850); and days of mechanical ventilation (DMV) as estimated by Kaplan–Meier curve 22 days (95% confidence interval: 14.2–29.8). We observed a statistically significant negative association between DMV and GA at birth (rho = − 0.587, p = 0.017), SA (rho = − 0.629, p = 0.009) and SW (rho = − 0.737, p = 0.001). One patient experienced left laryngeal nerve palsy confirmed by laryngoscopy. Otherwise, there were no adverse events to include surgical-related mortality, recurrence of PDA, or need for chest tube placement during follow-up. SL of PDA in ELBW infants without chest tube placement is both efficient and safe. Universal consensus recommendations for the management of PDA in ELBW neonates are needed. Further study is required regarding the use of the less invasive option of percutaneous PDA closure in ELBW infants.
Keywords: birth, premature; infant, extremely low birth weight; ductus arteriosus, patent; chest tube